2006
DOI: 10.4049/jimmunol.177.9.6062
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Tumor-Infiltrating Lymphocyte Effector Functions by the Homophilic Carcinoembryonic Cell Adhesion Molecule 1 Interactions

Abstract: Efficient antitumor immune response requires the coordinated function of integrated immune components, but is finally exerted by the differentiated effector tumor-infiltrating lymphocytes (TIL). TIL cells comprise, therefore, an exciting platform for adoptive cell transfer (ACT) in cancer. In this study, we show that the inhibitory carcinoembryonic Ag cell adhesion molecule 1 (CEACAM1) protein is found on virtually all human TIL cells following preparation protocols of ACT treatment for melanoma. We further de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 48 publications
(69 reference statements)
9
67
0
Order By: Relevance
“…This was in line with our findings that CEACAM1 protects melanoma cells and inhibits both activated NK cells (17) and activated T cells (19,20,24). Furthermore, we have recently shown an unusually high percentage of CEACAM1 þ circulating lymphocytes in the peripheral blood of patients with melanoma, as compared with healthy donors (24).…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…This was in line with our findings that CEACAM1 protects melanoma cells and inhibits both activated NK cells (17) and activated T cells (19,20,24). Furthermore, we have recently shown an unusually high percentage of CEACAM1 þ circulating lymphocytes in the peripheral blood of patients with melanoma, as compared with healthy donors (24).…”
Section: Introductionsupporting
confidence: 79%
“…We have previously shown that CEACAM1 homophilic interactions inhibit natural killer (NK) cell-mediated killing, independently of MHC class I recognition (16)(17)(18). We have further shown that CEACAM1 inhibits effector functions of TILs, such as cytotoxicity and IFNg release (19). Moreover, we found that an IFNg-driven upregulation of CEACAM1 on melanoma cells surviving TIL-mediated attack renders them even more resistant (20).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations